Dispersion, communication, and alignment: an experimental study of the emergence of structure in combinatorial phonology. Issue 2 (16th May 2020) - Roberts, Gareth; Clark, Robin
Abstract: Languages exhibit structure at a number of levels, including at the level of phonology, the system of meaningless combinatorial units from which words are constructed. Phonological systems typically exhibit greater dispersion than would be expected by chance. Several theoretical models have been proposed to account for this, and a common theme is that such organization emerges as a result of the competing forces acting on production and perception. Fundamentally, this implies a cultural evolutionary explanation, by which emergent organization is an adaptive response to the pressures of communicative interaction. This process is hard to investigate empirically using natural-language data. We therefore designed an experimental task in which pairs of participants play a communicative game using a novel medium in which varying the position of one's finger on a trackpad produced different colors. This task allowed us to manipulate the alignment of pressures acting on production and perception. Here we used it to investigate (1) whether above-chance levels of dispersion would emerge in the resulting systems, (2) whether dispersion would correlate with communicative success, and (3) how systems would differ if the pressures acting on perception were misaligned with pressures acting on production (and which would take precedence). We found that above-chance levels of dispersion emerged when pressures were aligned, but that the primary driver of communicative success was the alignment of production and perception pressures rather than dispersion itself. When they were misaligned, participants both found the task harder and (driven by perceptual demands) created systems with lower levels of dispersion.